Proportional Substitution of Chemical Fertilizers with Vermicompost on Growth and Production Potential of Onion (Allium cepa L.) - Mandal, Joydip; Ghosh, Chinanshuk; Chattopadhyay, G. N. (International Journal of Bio-resource and Stress Management, 2023)
An experiment was conducted at Horticulture Experiment and Demonstration Plot of Institute of Agriculture, Visva-Bharati, Sriniketan West Bengal, India during winter 2009-2010 to study the response of vermicompost (VC) and/or fertilizer NPK in various proportion on growth and yield of onion (Allium cepa L.). Significant variations were observed for different plant height, number of leaves, leaf girth, neck length and diameter, bulb polar and equatorial diameter, whole plant weight, average bulb weight and estimate yield per hectare. Application of 50% VC+50% NPK recorded maximum plant height, neck diameter, bulb polar and equatorial diameter, whole plant weight and average bulb weight. The same treatment also produced highest bulb yield (52.26 t ha-1). Application of organic inputs in combination with chemical fertilizer were found better option than application of organic manure or chemical fertilizer alone. Maximum (15.01) total soluble solid was registered for 100% VC treated plots. Proportional increase of VC application also increases the TSS value. Proportional increase of VC in the given plant nutrient also increase TSS value.